An Analysis of Asperger’s Syndrome in a Brilliant Young Mind (X+Y) Movie - Ni Putu Dhea Kirana Setia Widnyani; I Gusti Agung Sri Rwa Jayantini; Ida Bagus Gde Nova Winarta (LPPM Universitas Bumigora Mataram, 2022)
This research investigated the Asperger's Syndrome experienced by Nathan in A Brilliant Young Mind (X+Y) (2014) movie. Nathan is a nine-year-old boy who grew up with Autism Spectrum Disorder types called Asperger's Syndrome because he has shown two out of three main characteristics in the movie with six sub-characteristics included. With these characteristics, Nathan tends to have difficulties in mingling with society. The aim of this study is to identify the characteristics of Asperger’s syndrome that shows in A Brilliant Young Mind (X+Y) (2014) movie. The data in this research were taken from A Brilliant Young Mind (X+Y) (2014) movie and script directed by Morgan Matthews. In analyzing this movie, the theory formulated by Mesibov, Shea & Adams (2001) was used to analyze the characteristics of Asperger's Syndrome that Nathan suffered. This research used the qualitative method. The finding shows that there are six sub-characteristics of the Asperger's Syndrome that Nathan has; impairment in multiple nonverbal behaviors, difficulty in building a friendship, a lack of sharing pleasure, readability, or achievement with others, having social or temperamental retaliation, routines or ritual which never changes, and having an interest in a particular subject. Keywords: autism spectrum disorder, Asperger's syndrome, Asperger's syndrome’s characteristics, psychoanalysis